Cardioid oscillator-based pattern generator for imitating the time-ratio-asymmetrical behavior of the lower limb exoskeleton - Fu, Qiang; Luo, Tianhong; Cui, TingQiong; Ma, Xiangyu; Liang, Shuang; Huang, Yi; Wang, Shengxue (Frontiers in Neurorobotics, 2024)
Periodicity, self-excitation, and time-ratio-asymmetry are fundamental characters of the gait of the human being. In order to imitate these mentioned characters, a pattern generator with four degrees of freedom is proposed based on cardioid oscillators introduced by authors. The proposed pattern generator is composed of four coupled cardioid oscillators, which are self-excited and have asymmetric time ratios, and connected with other oscillators through coupled factors. On these bases, the dynamical behaviors of these oscillators, such as phase locking, time ratio, and self-exciting, are analyzed via simulations according to the harmonic balance method. Moreover, for comparison, the simulated trajectories are compared with the natural joint trajectories measured in experiments. Simulation and experiments resultsshow that the behaviors of the proposed pattern generator are similar to those of the natural lower limb. It means the simulated trajectories from the generator are self-excited generated without any additional inputs, they have the asymmetric time ratios, and their phases are locked with others. Moreover, the proposed pattern generator can be applied as the referenced model for the lower limb exoskeleton controlling algorithm, to produce the self-adjusted reference trajectories.Lower limb exoskeletons (LLEs) are the significant assist devices which can improve the movement ability of people with walking disabilities by controlling the movement of exoskeleton joints refer to the trajectories of the healthy human lower limbs [1][2][3][4][5][6][7]. Utilizing trajectory tracking control methods, due to the fitted trajectories from the gait data of the healthy human are invariant and nonadjustable, LLEs cannot adjust their reference swing angle curves according to the environment changes [8][9][10][11][12][13]. On the contrary, the reference trajectory generated by the central pattern generators (CPGs), a biological neural circuit that generates rhythmic behaviors in animals, is periodical and self-excited. What the mostly worth mention is that these trajectories possess the locked phase relationships and can be adjusted according to environment changes, which are attracted more and more researchers' attentions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].Recently, CPG models for imitating the swing angles of human lower limbs include neuron-based CPG model [14][15][16][17][18][19][20][21][22]. The former utilizes an oscillator to imitate the functions of neural cells,